HIV-1 subtype distribution in the Gambia and the significant presence of CRF49_cpx, a novel circulating recombinant form. - de Silva, T; Turner, R; Hué, S; Trikha, R; van Tienen, C; Onyango, C; Jaye, A; Foley, B; Whittle, H; Rowland-Jones, S; Cotten, M (2010)
BACKGROUND: Detailed local HIV-1 sequence data are essential for monitoring the HIV epidemic, for maintaining sensitive sequence-based diagnostics, and to aid in designing vaccines. RESULTS: Reported here are full envelope sequences derived from 38 randomly selected HIV-1 infections identified at a Gambian clinic between 1991 and 2009. Special care was taken to generate sequences from circulating viral RNA as uncloned products, either by limiting dilution or single genome amplification polymerase chain reaction (PCR). Within these 38 isolates, eight were subtyped as A and 18 as CRF02_AG. A small number of subtype B, C, D viruses were identified. Surprising, however, was the identification of six isolates with subtype J-like envelopes, a subtype found normally in Central Africa and the Democratic Republic of the Congo (DRC), with gag p24 regions that clustered with subtype A sequences. Near full-length sequence from three of these isolates confirmed that these represent a novel circulating recombinant form of HIV-1, now named CRF49_cpx. CONCLUSIONS: This study expands the HIV-1 sequence database from the Gambia and will provide important data for HIV diagnostics, patient care, and vaccine development.